Demulsification based on the thermal treatment (cooling and heating) of W/O emulsions - Rajaković Vladana N. (Hemijska Industrija, 2004)
An important step in waste water treatment is the removal of oil from an O/W emulsion and the separation of oil and water into two phases, a process usually called demulsification. Modern methods of oil removal from waste water were described in the present study. Typical demulsification techniques include thermal, electrical, chemical, acoustic, or mechanical methods of emulsion treatment. The freeze/thaw process was found to be very effective for demulsification. In the freeze/thaw process, water removal from the W/O emulsion depends on the initial oil content, freezing temperature, freezing time, thawing rate and temperature. The described method is a non-destructive and physical method of emulsion treatment and because there is no addition of chemical agents there is no problem of further waste water treatment, which usually exists when chemicals are applied for demulsification. Different methods for oil content determination in the O/W emulsion were also applied and compared in this study (gravimetric, volumetric, measurement of oxygen consumption and emulsion pH, IR analysis of the emulsion, electro analytical measurement).